A STUDY ON ASSESSMENT OF KNOWLEDGE REGARDING CAUSES AND EARLY SYMPTOMS OF DEPRESSION AMONG RURAL WOMEN IN A SELECTED COMMUNITY AT SRI GANGANAGAR - Kaushalya; Arora, Jyoti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Introduction: Depression is a leading global mental health concern and a major contributor to disability worldwide. Women, particularly in rural areas, are disproportionately affected due to various socio-economic and psychosocial factors. In India, limited mental health literacy, stigma, and lack of access to services contribute significantly to undiagnosed and untreated depression among rural women. This study was conducted to assess the knowledge of rural women regarding the causes and early symptoms of depression in a selected community at Sri Ganganagar. Methodology: A quantitative research approach with a descriptive survey design was adopted. The study was conducted in Netewala Sri Ganganagar. A sample of 100 women aged between 35 to 60 years was selected using a purposive sampling technique. Data were collected through a structured interview schedule comprising two sections: socio-demographic profile and knowledge-based questions on causes and early symptoms of depression. The tool’s reliability was established using the split-half method with a reliability coefficient of 0.82. Results: The findings revealed that 55.04% of respondents had knowledge of symptoms, while 48.48% had knowledge of causes. In terms of overall knowledge, 56% had poor knowledge, 31% had good knowledge, and only 13% had excellent knowledge. Awareness about depression was reported by 29% of respondents, with mass media (24%) being the most common source of information. A statistically significant association was found between knowledge level and variables such as age, education, income, occupation, and awareness source. Conclusion: The study highlights a considerable gap in mental health literacy among rural women. Focused educational initiatives and integration of mental health awareness into rural health programs are crucial to empower women with timely recognition and help-seeking behavior.